Marketing as strategy : understanding the CEO's agenda for driving growth and innovation - Kumar, Nirmalya (Boston, Mass. : Harvard Business School Press, 2004)
"Today's Marketers face a dire situation. CEOs name marketing challenges such as retaining customers and avoiding price wars as top priorities, yet they increasingly doubt whether marketers can handle those challenges. Marketing's traditional goal - getting close to customers - has become the organization-wide mandate, yet marketing as a function has lost importance. Once viewed as a critical expenditure, marketing is now considered a cost sink. What happened? More important, what can marketers do to regain a prominent role in their organizations?" "Nirmalya Kumar argues that the only way for marketers to get back on the CEO's agenda is to tackle issues that merit the CEO's attention - and conducting market research and placing ads don't make the cut. The fate of marketing hinges on elevating the role of marketing executives from promotions-focused tacticians to customer-focused leaders of transformational initiatives that are strategic, cross-functional, and bottom-line oriented."--BOOK JACKET.
From marketing as a function to marketing as a transformational engine -- From market segments to strategic segments -- From selling products to innovating solutions -- From declining to growing distribution channels -- From branded bulldozers to global distribution partners -- From acquiring to rationalizing brands for profit -- From market-driven to market-[d]riving -- From strategic business units to corporate marketing.
Includes bibliographical references (pages [247]-258) and index.
Description based on print version record.
Keywords: Marketing; Strategic planning; Marketing; Strategische planning; Marketing; Planification stratégique; Marketing; Strategic planning; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books